2004
DOI: 10.1158/1078-0432.ccr-04-0690
|View full text |Cite|
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor (EGFR) Is Overexpressed in Anaplastic Thyroid Cancer, and the EGFR Inhibitor Gefitinib Inhibits the Growth of Anaplastic Thyroid Cancer

Abstract: Purpose: No effective treatment options currently are available to patients with anaplastic thyroid cancer (ATC), resulting in high mortality rates. Epidermal growth factor (EGF) has been shown to play a role in the pathogenesis of many types of cancer, and its receptor (EGFR) provides an attractive target for molecular therapy.Experimental Design: The expression of EGFR was determined in ATC in vitro and in vivo and in human tissue arrays of ATC. We assessed the potential of the EGFR inhibitor gefitinib ("Ire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(99 citation statements)
references
References 29 publications
(22 reference statements)
5
91
0
2
Order By: Relevance
“…In agreement with this, EGFR and VEGFR2 overexpression has been shown to be closely correlated to advanced tumor stage, metastasis, and poor clinical outcome in several human cancers. With respect to thyroid carcinomas, EGFR overexpression has been detected in most anaplastic tumors (Schiff et al 2004, Wiseman et al 2007, Elliott et al 2008 and to a much lower extent in PTCs (Schiff et al 2004, Murakawa et al 2005, Mitsiades et al 2006, Lim et al 2007, Elliott et al 2008. In PTC, EGFR expression has been associated to poor prognosis (Akslen & Varhaug 1995, Chen et al 1999, although not always (Lim et al 2007), and recent studies have suggested that EGFR inhibitors might be active against anaplastic thyroid carcinomas (Lopez et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, EGFR and VEGFR2 overexpression has been shown to be closely correlated to advanced tumor stage, metastasis, and poor clinical outcome in several human cancers. With respect to thyroid carcinomas, EGFR overexpression has been detected in most anaplastic tumors (Schiff et al 2004, Wiseman et al 2007, Elliott et al 2008 and to a much lower extent in PTCs (Schiff et al 2004, Murakawa et al 2005, Mitsiades et al 2006, Lim et al 2007, Elliott et al 2008. In PTC, EGFR expression has been associated to poor prognosis (Akslen & Varhaug 1995, Chen et al 1999, although not always (Lim et al 2007), and recent studies have suggested that EGFR inhibitors might be active against anaplastic thyroid carcinomas (Lopez et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is also frequently overexpressed in various types of thyroid carcinomas (11 -16) and this overexpression has been shown to correlate with poor prognosis in several studies (17,18). Recent work from our laboratory has shown that EGFR is overexpressed in ATC tumors as well (19). Consistent with these observations, inhibition of EGFR by using an anti-EGFR antibody and a small-molecule inhibitor of EGFR tyrosine kinase, AG 1478, has shown antiproliferative effects against thyroid carcinoma cell lines in vitro (20,21).…”
Section: Introductionmentioning
confidence: 96%
“…EGFR is overexpressed in ATC cell lines in vitro and in vivo as well as human ATC specimens (Schiff et al 2004). Gefitinib inhibited cellular proliferation and induced apoptosis in ATC cell lines and slowed tumor growth in a nude mouse model of subcutaneous implant of ATC.…”
Section: Gefitinibmentioning
confidence: 98%